Rapid assessment of the main economic value indicators in lupine flour samples using infrared spectroscopy - V. S. Popov; A. V. Salikova; I. N. Perchuk; N. G. Konkova; G. P. Egorova; M. A. Vishnyakova; T. V. Shelenga (Труды по прикладной ботанике, генетике и селекции)
Background. A calibration model has been developed for rapid assessment of economic value indicators (protein, oil, and quinolizidine alkaloid contents) in the seeds of narrowleaf lupine accessions from VIR using near-infrared spectroscopy, with the help of which it is possible to decide on the further use of the accessions.Materials and methods. Biochemical quality indicators (protein, oil, and quinolizidine alkaloid content) were studied in the seeds of narrowleaf lupine (Lupinus angustifolius L.) grown in 2019 in the northwest of Russia. Calibration models for measuring protein, oil and alkaloids in lupine seeds (62 accessions) were developed using a MATRIX-I IR analyzer (Bruker Optics, Germany). To construct calibration models, we used the values obtained by chemical analysis methods accepted at VIR. The oil content in lupine seeds was assessed by the defatted dry residue technique in Soxhlet extractors, protein by the Kjeldahl method, and quinolizidine alkaloids by gas chromatography coupled with mass spectrometry. All indicators were recalculated on the dry-weight basis.Results and conclusion. Statistical significance of the developed models was verified according to the results of measuring the content of protein, oil and alkaloids in the seeds of the test batch. The protein and oil content data obtained using a calibration curve did not differ significantly from the results of chemical studies, in contrast to alkaloid indicators. Consequently, the developed calibration model for the MATRIX-I IR analyzer can be used for rapid assessment of protein and oil content in narrowleaf lupine flour samples, thus accelerating the process of obtaining data on the main economic value indicators. The analysis does not require reagents and is safe.